Diversification of the tropical African flora : spatial and temporal approaches - (:unkn) unknown (My University, 2021)
This thesis investigates the diversification of the tropical African flora, through different spatial and temporal approaches. The current patterns of distribution of the species across the continent are the result of various environmental changes, and we investigated how these changes affected the flora using the geographical distribution of the species, molecular phylogenies, and several various biogeographic and diversification models. The thesis can be divided in 2 great parts of different spatial and taxonomic scales.The first part is at large geographical and taxonomic scale, and focuses on the whole flora across the continent. In the Chapter 2, we described the patterns of plant endemism in tropical Africa, and identified ‘cradles’ (regions with significantly more recently diverged taxa) and ‘museums’ (regions with significantly more anciently diverged taxa) of angiosperm diversity at the generic level. We show that the montane areas of the biogeographically complex region of Eastern Africa are both cradles and museums of diversity, underlining the important role played by mountains in the diversification of the flora. In contrast, the Guineo-Congolian lowland rain forest region is characterised by widespread and old lineages.The second part of the thesis reduces the geographical and taxonomic scales. It focuses on the species rich African tropical rain forests (TRF) and their evolution, informed by the study of the Monodoreae tribe (Annonaceae), a clade of 92 plant species restricted to the TRF. To do so, the systematic and taxonomy of the Monodoreae need to be well resolved, especially for the two genera Uvariodendron and Uvariopsis that lack a recent revision. Thus, the Chapter 3 is dedicated to the systematic of the Monodoreae, for which we reconstructed a robust phylogenetic tree using more than 300 nuclear genes. Our results support systematic changes, such as the erection of the Ophryptealeae tribe, the reinstatement of the monoty
Keywords: African Research